Analytical design model for waste heat thermoelectric generator and experimental verification. (15th January 2022) - Li, Guoneng; Ying, Jie; Zheng, Youqu; Guo, Wenwen; Tang, Yuanjun; Ye, Chao
Highlights: An analytical design model for waste heat thermoelectric generator is developed. The developed model interlinks the material, device, and system levels. The developed model is verified by experiments and the accuracy is 15.3%. The designed experimental prototype with 24 modules has excellent performance. The prototype generates an electric power of 96.6 W with a pressure drop of 375 Pa. Abstract: Low conversion efficiency of power systems and carbon emission induced climate crisis boost extensive investigations on waste heat utilization, particularly studies of converting waste heat into high-grade electric energy. Thermoelectric generator (TEG) is such a potential solution to abovementioned technical demand. An analytical design model for waste heat TEG, interlinking the underlying three different levels (material, device, and system), is not reported yet though a large number of previous researches intensively studied various important aspects of waste heat TEG with theoretical, numerical and experimental methods. The analytical design model, firstly developed in this work, constructs a straightforward but thoughtful bridge to interlink material, device, and system levels of waste heat TEG, providing multilevel-coupled heat collection surface area, expected electric power outcome, and resulting pressure drop. A high performance customized waste heat TEG can be readily obtained using the present analytical design model with necessary boundary inputs. The effectiveness and accuracy are verified through experimental data. A waste heat TEG prototype with 24 TE modules, exactly machined and assembled according to the developed analytical design model, shows superior performance when compared to previous TEGs. The abovementioned TEG generates an electric power of 96.6 W with a pressure drop of 375 Pa under the exhaust gas temperature of 648 K. Comprehensive discussions are presented to indicate limitations and applications of the developed analytical design model.